Photomorphogenesis, B-Box transcription Factors, and the legacy of Magnus Holm - Bowler, Chris (2013)
Fil: Bowler, Chris. Ecole Normale Superieure. Institut de Biologie. Environmental and Evolutionary Genomicsm; Francia